2017
DOI: 10.3762/bjoc.13.136
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of 5,11-dihydroindolo[3,2-b]carbazoles and synthetic applications of their nitro-substituted derivatives

Abstract: A new general approach to double nitration of 6,12-di(hetero)aryl-substituted and 6,12-unsubstituted 5,11-dialkyl-5,11-dihydroindolo[3,2-b]carbazoles by acetyl nitrate has been developed to obtain their 2,8-dinitro and 6,12-dinitro derivatives, respectively. A formation of mono-nitro derivatives (at C-2 or C-6) from the same indolo[3,2-b]carbazoles has also been observed in several cases. Reduction of 2-nitro and 2,8-dinitro derivatives with zinc powder and hydrochloric acid has afforded 2-amino- and 2,8-diami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…305 It has also been demonstrated that bromo-substituted indolo [3,2-b]carbazoles are good substrates in Heck reactions with 2-vinylpyridine 306 or 4-(N,N-diphenylamino)styrene. 298 Techniques are now also available for selective formylation and acylation of indolo 312 As illustrated above (Scheme 71), formyl derivatives are also accessible by means of halogen−metal exchange, followed by quenching of the resulting lithiated species with DMF, enabling introduction of the formyl group into indolo [3,2-b]carbazoles at C-2, 243,273 C-3, 273 and simultaneously at C-2/C-8. 244,257 In a sequence relying on a selective halogen-metal exchange as the key transformation, the readily available indolo [3,2-b]carbazole 324 (prepared by Fischer indolization and subsequent Nalkylation) was converted to the formyl derivative 325 in good yield.…”
Section: Synthesis and Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…305 It has also been demonstrated that bromo-substituted indolo [3,2-b]carbazoles are good substrates in Heck reactions with 2-vinylpyridine 306 or 4-(N,N-diphenylamino)styrene. 298 Techniques are now also available for selective formylation and acylation of indolo 312 As illustrated above (Scheme 71), formyl derivatives are also accessible by means of halogen−metal exchange, followed by quenching of the resulting lithiated species with DMF, enabling introduction of the formyl group into indolo [3,2-b]carbazoles at C-2, 243,273 C-3, 273 and simultaneously at C-2/C-8. 244,257 In a sequence relying on a selective halogen-metal exchange as the key transformation, the readily available indolo [3,2-b]carbazole 324 (prepared by Fischer indolization and subsequent Nalkylation) was converted to the formyl derivative 325 in good yield.…”
Section: Synthesis and Reactionsmentioning
confidence: 99%
“…Likewise, other N -alkylated indolo­[3,2- b ]­carbazoles displayed these reactivity patterns, including 5,11-diethyl-5,11-dihydroindolo­[3,2- b ]­carbazole, eventually allowing corroboration of the structures of several of its nitration/bromination products by single-crystal X-ray diffraction. Synthetically useful examples of displacement reactions of the nitro groups at C-6 and/or C-12 by thiolate salts or nitrogen nucleophiles were also included in this thorough study, which addresses a previously poorly explored but potentially important facet of the chemistry of indolo­[3,2- b ]­carbazoles …”
Section: Indolo[32-b]carbazolesmentioning
confidence: 99%
“…Thus, we have recently described a number of convenient synthetic procedures for regioselective formylation, acylation, aroylation and nitration of 5,11-dialkyl-6,12-di(hetero)aryl-substituted indolo [3,2-b]carbazoles at C-2 and C-8 positions, and demonstrated usefulness of the obtained functional ICZ derivatives as building blocks for construction of more complex π-conjugated and fused molecules. [27][28][29][30][31]…”
Section: Introductionmentioning
confidence: 99%
“…The indolo­[3,2- b ]­carbazole (ICZ) framework exists in natural products (such as malasseziazoles A–C), optoelectronic materials, and biologically active molecules . As a consequence, a plethora of synthetic methods for the construction of these ICZs have been reported. , They mainly rely on (i) the formation of two pyrrole rings from substituted p -phenylenediamine, terphenyl, or cyclohexane-1,4-dione bis­(phenylhydrazone) derivatives, (ii) the formation of the central ring from indole or bis­(indolyl)­methane derivatives, and (iii) modification of the preformed ICZs . Despite intensive research efforts, most of these methods have been applied to the synthesis of symmetrical ICZs. , Therefore, the development of general and efficient strategies for the rapid synthesis of unsymmetrical ICZs, especially those with diverse functional groups at both terminal benzene rings, is still highly desirable.…”
mentioning
confidence: 99%